Late-onset Pompe disease with complicated intracranial aneurysm: a Chinese case report - Zhang B; Zhao Y; Liu J; Li L; Shan J; Zhao D; Yan C (Neuropsychiatric Disease and Treatment)
Bin Zhang,1,2,* Yuying Zhao,1,3,* Junling Liu,1,4 Ling Li,1 Jingli Shan,1 Dandan Zhao,1 Chuanzhu Yan1,3 1Laboratory of Neuromuscular Disorders and Department of Neurology, Qilu Hospital of Shandong University, Jinan, Shandong, 2Department of Neurology, Liaocheng People’s Hospital, Liaocheng, Shandong, 3Department of Neurology, Qilu Hospital of Shandong University, Key Laboratory for Experimental Teratology of the Ministry of Education, Brain Science Research Institute, Shandong University, Jinan, Shandong, 4Department of Neurology, Affiliated Hospital of Weifang Medical University, Weifang, Shandong, People’s Republic of China *These authors contributed equally to this work Abstract: Pompe disease is a rare autosomal recessive hereditary disease caused by genetic defects of acid maltase. This disease could be divided into two forms: infantile and late-onset, which mainly affect cardiac, respiratory, and skeletal muscle systems. Late-onset patients mainly show symptoms of skeletal muscle involvement, but recent reports have found that the central nervous system was also affected in some patients. Herein, we report a case of a female, adolescent-onset Pompe patient, who was diagnosed with complicated intracranial aneurysm in adulthood. Keywords: Pompe disease, glycogen storage disease II, acid maltase, acid alpha-glucosidase, cerebrovascular disorders